Penerapan Metode Demontrasi dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam (PAI) Siswa Kelas XI SMA Negeri 1 Metro TA 2019/2020 - Nurhasim (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2021)
Problems in the implementation of learning cause students' learning outcomes are not good. As for example, the implementation of learning is still centered on the teacher, is conventional by using the lecture system in full, the emphasis is not on facts and information, but rather emphasizes on memorization, attaches more importance to the content than the process, and is less directed at meaningful and functional learning for the lives of students. The learning process that does not involve students in the real world and does not realize interaction between students, making it less interesting, boring, students become passive, as a result of which students can not master the material well. To overcome all of that, researchers applied new media as a way to increase students' learning interest, namely by using demonstration methods. The issue was discussed through class action research conducted through two cycles. Research data obtained through observation in the classroom and documentation of the results of actions taken as well as data from class teachers. From the results of the study obtained an increase in each cycle, namely on the increase in the average grade of students in the pre-cycle is 66.77 in cycle I: 75.00 and 80.00 in cycle II. The percentage of students' learning completion also increased, namely 62.06% in pre-cycle, 79.31% in cycle I, and 100% in cycle II. Thus, the increase in learning completion from pre-cycle to cycle I after improvement was 17.25%, and increased from cycle I to cycle II by 20.69%.